BINH DUONG LACQUER COMBINES TRADITION AND MODERNITY (Proceeding of the International Conference on Arts and Humanities, 2024)
It might be argued that any Vietnamese has the right to be proud of the magnificent beauty of the golden light, the iridescence of clams and eggs, and the depth of bright red and deep blue colors in lacquer Vietnam paintings. Furthermore, traditional lacquer in Binh Duong province, Vietnam, is no exception to such aesthetic flow and is no less unique, capturing spectators' attention in a fascinating and bizarre manner. Today, the majority of residents in Tuong Binh Hiep lacquer hamlet in Binh Duong province specialize in producing gold-plated lacquer to provide for the basic needs of the region and the entire country of Vietnam. At the same time, they have developed works that have both memento value, which helps to build craft villages and tourism, and high creative value, which is worthy of prominent artists in craft villages. The author of the article combined the interdisciplinary research method of history and cultural studies with the fine art method, analyzing migration, acculturation, and historical data on the formation and development of lacquer in Binh Duong province through works such as Thanh Le lacquer, Tuong Binh Hiep lacquer, and Dinh Hoa lacquer. At the same time, the author of the article examines the features of artistic language to highlight the traditional and modern qualities that are always present in lacquer paintings in Binh Duong province. It needs to be understood and underlined so that future generations can inherit, promote, and protect the local national cultural identity.
Keywords: Binh Duong Lacquer; modern; Tuong Binh Hiep Lacquer village; traditional